A multidisciplinary team approach minimises prophylactic mastectomy rates. Issue 8 (August 2015) - Leff, D.R.; Ho, C.; Thomas, H.; Daniels, R.; Side, L.; Lambert, F.; Knight, J.; Griffiths, M.; Banwell, M.; Aitken, J.; Clayton, G.; Dua, S.; et al.
Abstract Background Prophylactic mastectomy (PM) has become increasingly common but is not without complications especially if accompanied by reconstructive surgery. In patients with sporadic unilateral breast cancer, contralateral PM offers no survival advantage. Multidisciplinary team (MDT) communication and interaction may facilitate shared decision-making and curtail PM rates. The aim of this study was investigate the effect of a regional MDT meeting on PM decision-making. Methods We conducted an observational study involving retrospective review of prospectively recorded MDT meeting records for a 151 patient requests for PM from 2011 to 2014. Final MDT decisions were recorded as PM 'accepted', 'declined' or 'pending'. For MDT sanctioned requests, the factors justifying PM were recorded. Where PM was declined, justification for MDT refusal was sought and recorded. Results Approximately half of all requests for PM have been upheld (53.0%) and 1/3 of requests have been declined (32.5%). Of those declined, low risk of contralateral breast cancer versus relatively high risk of systemic relapse were commonly cited as justification for PM refusal (45.7%). A proportion of patients who initiated PM discussion subsequently changed their minds (19.6%), or failed to attend clinic appointments (6.5%). Some patients were deemed medically unfit for complex reconstructive surgery (13%), or were declined on the basis of an apparent cosmetic drive for surgery (6.5%), concerns regarding depression or anxiety (2.2%) and/or if family history could not be substantiated (6.5%). Discussion MDT meetings facilitate cross-specialty interrogation of requests for PM, minimise unnecessary surgery and restrict PM to those likely to derive maximum benefit.